A nuclear option for power and desalination on Madura Island. (4th October 2004) - Djokolelono, Mursid; Soentono, Soedyartomo; Hastowo, Hudi
Madura Island, which comprises 5.3 thousand square kilometres and is inhabited by 3.1 million people, belongs to the East Java Province of Indonesia. Proximity to the congested Surabaya city-port makes Madura enticing as a place to accommodate the expansion of port facilities and industrial estates operating in Surabaya. Efforts to support industrial development have been made, e.g. in the construction plan for a 6 km connecting bridge as well as in respect of power and water reliance. Power demand has been predicted to reach 119 to 136 MW by 2007 and 221 to 292 MW by 2015. Since electricity to the island is connected to the Jawa-Bali grid, system expansion can be solved within the Jawa-Bali expansion-planning scheme. In 1998, however, the breakage of the submarine power cables resulted in a blackout of the whole island for forty days, which encouraged planners to launch the idea of a self-reliance scenario within the island. Fossil power plants (100 to 200 MW) are sought to become candidate solutions for 2007, whereas a nuclear alternative comes into consideration for 2015. Their are four water municipalities (Regencies), which in total produce clean water equivalent to 120 L/capita/day for only 5.8% of the inhabitants with a distribution loss of 18-35%. It is obvious that water demand is suppressed and that the quantity required, on which to base planned expansion, depends upon the amount of industrial development. The present water capacity required to meet the four Regencies' demands ranges from 18, 000-23, 000 m³/day. However, since water supply solutions are limited to each locality (and not integrated for the whole of Madura), the expansion plan can only start by aiming for a modest capacity increase, which is sought to be around 4, 000 m³/day in 2007 growing over the years with unit additions. Should a power and desalination plant be built, the rejected brine would become a useful input to salt production, enabling traditional methods (used on the island for a long time) to lower costs by 19% and create 36% more efficient land-use. A preliminary economic assessment to this date denotes a gas-fuelled combined cycle plant to be the best candidate to power the project, thanks to the availability of gas basins offshore near to Madura Island. This nuclear alternative is sought to come into competition with the fossil ones in 2015, being the nearest possible introduction to the island deployment. Additional requirements, however, to the design of the nuclear plant and its safety features to accommodate the local environment are crucial. Tripartite cooperation with the KAERI and the IAEA is proceeding to provide assistance with the study of technologies and expertise for the project.